Disturbance Observer Based Control of Multirotor Helicopters Based on a Universal Model with Unstructured Uncertainties. (22nd March 2015) - Xie, Ye; Cao, Yunfeng; Wang, Biao; Ding, Meng
Abstract : To handle different perspectives of unstructured uncertainties, two robust control techniques on the basis of a universal model are studied in this paper. Rather than building a model only applicable to a specific small-scale multirotor helicopter (MHeli), the paper proposes a modeling technique to develop a universal model-framework. Particularly, it is straightforward to apply the universal model to a certain MHeli because the contribution and allocation matrix is proposed in the model-framework. Based on the model uncertainties, the load perturbation of the rotor is the primary focus due to its indispensable importance in the tracking performance. In contrast to the common methods, it is proposed to take this unstructured uncertainty in that external disturbance and designs disturbance observer (DOB). In addition, a class of lead-compensator is specifically designed as for compensating phase lag induced by DOB. Compared withH ∞ loop-shaping, greater robust tracking performance on rejecting load perturbation could be achieved as a tradeoff between robust stability and tracking performance which is successfully avoided with DOB-based control strategy.